The Indian textile sourcebook : patterns and techniques - Fotheringham, Avalon; Victoria and Albert Museum; V&A Publishing (New York, New York : Thames & Hudson ; London : V&A, 2019)
"Indian textile designs express dazzling inventiveness and creativity, from the woven silks of royalty to the simple block-printed patterns. This authoritative sourcebook overflows with colour and patterns to inspire and inform. The introduction gives an overview of Indian textiles, including methods by which they were made and their intended uses. The book is divided into three chapters defined by pattern style: Florals, Figurative and Geometric. Each comprises an introduction to the style's history, and demonstrates the techniques of structure, surface and embellishment patterning. A wealth of cross-referencing by theme and process makes this a uniquely useful resource. Over 300 breathtaking and hugely varied designs are examined here in detail through close-up shots of the pattern and material alongside a thoughtful examination of the reverse of many fabrics, demonstrating different weaving techniques so that the reader can see precisely how the textile was made." -- V&A website.
Overview of techniques -- Floral patterns -- Figurative patterns -- Abstract and geometric patterns.
"All pictures V&A unless otherwise stated"--Colophon.
boek
Keywords: Victoria and Albert Museum; India